1985
DOI: 10.1080/00071668508416782
|View full text |Cite
|
Sign up to set email alerts
|

Circulating prolactin concentrations in chickens infected withEimeria tenella

Abstract: 50000 oocysts of Eimeria tenella were inoculated into three-week-old cockerels and the effect of the infection (coccidiosis) on circulating concentrations of glucose, prolactin, sodium, potassium and haematocrit was determined. At day 5 of infection haematocrit was reduced and glucose was increased. From day 7 onwards prolactin concentration was elevated in infected birds compared with control and pair-fed birds. Plasma electrolytes were unchanged. It appears likely that loss of water resulting in osmotic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…As in mammals, circulating prolactin levels have classically been reported to increase in response to stress in early studies of birds Scanes and Harvey, 1981). For instance, prolactin levels increase in response to cold or immobilization stress in domestic birds (Harvey et al, 1977(Harvey et al, , 1978Opel and Proudman, 1986) and the stress of a high parasite load or an infection results in increased prolactin levels in domestic fowls (Chadwick et al, 1985;Davison et al, 1985). Interestingly, Opel and Proudman (1986) reported that prolactin levels respectively increase and decrease in non-breeding and incubating turkeys, suggesting that the prolactin stress response differs dramatically between nonbreeders and parents.…”
Section: Stage-dependent Prolactin Stress Responsementioning
confidence: 97%
“…As in mammals, circulating prolactin levels have classically been reported to increase in response to stress in early studies of birds Scanes and Harvey, 1981). For instance, prolactin levels increase in response to cold or immobilization stress in domestic birds (Harvey et al, 1977(Harvey et al, , 1978Opel and Proudman, 1986) and the stress of a high parasite load or an infection results in increased prolactin levels in domestic fowls (Chadwick et al, 1985;Davison et al, 1985). Interestingly, Opel and Proudman (1986) reported that prolactin levels respectively increase and decrease in non-breeding and incubating turkeys, suggesting that the prolactin stress response differs dramatically between nonbreeders and parents.…”
Section: Stage-dependent Prolactin Stress Responsementioning
confidence: 97%
“…Meanwhile, PRL levels alters in different chicken breeds (Mo et al, 2022 ). When chickens are infected with pathogens, such as Histomonas meleagridis (Chadwick et al, 1980 ), E. tenella (Chadwick et al, 1985 ), and ALV-J (Mo et al, 2021 ), the plasma PRL levels have changed compared with the uninfected chickens. These results indicate that PRL levels is not only affected by individual own growth cycle but also controlled by external factors.…”
Section: Prolactin and The Immune Systemmentioning
confidence: 99%
“…In poultry, PRL and GH are related to growth, development, and reproduction (Nie et al, 2005 ; Qin et al, 2013 ; Wilkanowska et al, 2014 ). However, some studies have shown that after chicken infected with some pathogens, such as Eimeria tenella ( E. tenella ) (Chadwick et al, 1985 ; Davison et al, 1985 ), Histomonas meleagridis (Chadwick et al, 1980 ), infectious bronchitis virus (IBV) (Nii et al, 2015 ), Newcastle disease virus (NDV) (Rehman et al, 2020 ), infectious bursal disease virus (IBDV) (He et al, 2018 ; Yu et al, 2019 ), Marek's disease virus (MDV) (Liu et al, 2001 ) and avian leukosis virus (ALV) (Carter and Smith, 1983 , 1984 ; Dai et al, 2019 ; Mo et al, 2021 , 2022 ), it is found that the hormone levels are changed, and they are involved in regulating the body immune response (Allen et al, 1997 ; Breuel et al, 2004 ; Hartwell et al, 2014 ; Yu et al, 2020 ; Hu et al, 2021 ). These evidences suggest that hormones are involved in the immune responses under specific conditions, which present an often-overlooked challenge to the conventional idea that hormone merely as endocrine hormone.…”
Section: Introductionmentioning
confidence: 99%
“…tenella ile enfekte olmuş hayvanlarda kanamalara bağlı olarak bazı biyokimyasal ve hematolojik parametrelerde sağlıklı hayvanlara göre önemli değişiklikler olabileceği bildirilmiştir 8.12 . Deneysel olarak E. tenella ile enfekte edilen tavuklarda total protein ile alyuvar düzeylerinde 8 , hematokrit 5,8,35 ve hemoglobin düzeyinde 20 önemli bir azalma olduğu ve bunun nedeninin de laina propria'da gelişen ikinci nesil merontların damar duvarlarına yaptıkları mekanik hasar ve bağırsak epitel hücrelerinin yıkımına bağlı olarak oluşabileceği belirtilmiştir. Benzer şekilde bu çalışmada da total protein, albumin, alyuvar, hematokrit ve hemoglobin değerlerinde şiddetli kanamalara bağlı olarak önemli düşüşler tespit edilmiştir.…”
Section: Tartışma Ve Sonuçunclassified